2014
DOI: 10.1017/s0967199414000239
|View full text |Cite
|
Sign up to set email alerts
|

Insulin influences developmental competence of bovine oocytes cultured in α-MEM plus follicle-simulating hormone

Abstract: The aim of this study was to evaluate the dose-response effect of insulin, plus follicle-simulating hormone (FSH) at a fixed concentration, in a serum-free defined culture medium (DCM) on the in vitro maturation of bovine cumulus-oocyte complexes (COCs). For oocyte nuclear maturation, the expression levels of GDF9, GLUT1, PRDX1 and HSP70.1 transcripts related to oocyte and embryo developmental competence were analysed. For in vitro maturation (IVM), cumulus-oocyte complexes from slaughterhouse ovaries were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(91 reference statements)
2
5
0
Order By: Relevance
“…The in vitro rates of embryo development were similar to those described by Mota et al (2015), and no differences were observed between 0FSH and 0FSH 100LY groups (Fig. 6).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The in vitro rates of embryo development were similar to those described by Mota et al (2015), and no differences were observed between 0FSH and 0FSH 100LY groups (Fig. 6).…”
Section: Resultssupporting
confidence: 86%
“…Polar body extrusion is strongly influenced by FSH (Mota et al, 2015) and PI3K. The F-actin in oocytes is dependent on PtdIns(3,4,5)P3, which is produced by proteins such as PI3K.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two media were used. Medium I was α-minimum essential medium (α-MEM) and was used as a control medium [ 21 ]. Medium II was hUCM [ 22 ].…”
Section: Methodsmentioning
confidence: 99%